Efficiency of Zinc (II) Metal Ion Adsorption Using Fe3O4/Clay Composites from Bangka - Ayu Ratna Sari; Verry Andre Fabiani; Nurhadini Nurhadini (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Research on the adsorption efficiency of Zn2+ metal ions has been carried out using a composite Fe3O4-clay from Bangka. This study aims to determine the characteristics of Fe3O4-clay composites using FTIR and XRD, determine the adsorption efficiency of Zn2+ metal ions by activated natural clay, Fe3O4, and Fe3O4-clay composites (1:1, 1:2 and 1:3) and determine the effect of concentration. on the adsorption efficiency of Zn2+ metal ions by the Fe3O4-clay composite. The results of FTIR and XRD analysis showed that the Fe3O4-clay composite was successfully synthesized. Based on the results of characterization by FTIR on Fe3O4-clay, it shows the formation of composites with the absorption peak at wave numbers 3685 cm-1 and 683,89 cm-1 which were absorption peaks of clay and at wave number 3448,32 cm-1 is the absorption peak. This absorption peak allowed to bind with clay. In addition, the XRD analysis results of Fe3O4-clay composite showed a diffraction peak at 2θ = 12,23o; 20,83o; 24,83o; 26,6o; 30,48o; 35,625o and 62,5o which consist of clay and Fe3O4. The adsorption efficiency of activated natural clay, Fe3O4, Fe3O4-clay (1:1, 1:2 and 1:3) could absorb Zn2+ metal ions, respectively 99,18%, 44,76%, 99,25%, 94,63% and 76,25%, with the highest adsorption efficiency found in the Fe3O4-clay composite (1:1). The adsorption efficiency of Zn2+ metal ions by the Fe3O4-clay (1:1) composite reached 49,57% at a Zn2+ metal ion concentration of 20 mg/L.